Hearing Loss and Healthcare Access among Adults - Mahmoudi, Elham; Zazove, Philip; Pleasant, Terrence; Meeks, Lisa; McKee, Michael M. (Seminars in Hearing, 2021)
Hearing loss (HL) is common among individuals aged 50 and older and is associated with increased healthcare costs. Whether HL is associated with less access to healthcare is unclear. In this study, we examined the association between HL and access to medical care and prescription drugs among individuals 50+ with and without HL. We used nationally representative 2013–2014 Medical Expenditure Panel Survey data, consisting of 1,977 adults with HL and 17,399 without. We applied an inverse propensity score weighting and regression modeling to adjust for any potential differences in health and socioeconomic conditions between the two groups. Adults with HL were more likely to be white, less educated, poorer, and with public insurance (p < 0.001). They were also likely to have hypertension, heart disease, stroke, emphysema, high cholesterol, diabetes, joint pain, and arthritis (p < 0.001). The odds of reporting unmet medical needs (odds ratio [OR] = 1.85; 95% confidence interval [CI] = 1.29–2.66), delay in getting medical needs met (OR = 1.37; 95% CI = 1.00–1.87), and having unfilled prescriptions (OR = 1.81; 95% CI = 1.27–2.59) were higher among individuals with HL compared with their counterparts without HL. Individuals with HL have less access to care and prescription drugs. To ensure equitability in access, public health policies should address specific needs of people with HL.
Keywords: hearing loss; healthcare access; medical expenditure panel survey